Conceptualizing strategic environmental assessment: Principles, approaches and research directions - Noble, Bram; Nwanekezie, Kelechi (Environmental impact assessment review, 2017)
Increasing emphasis has been placed in recent years on transitioning strategic environmental assessment (SEA) away from its environmental impact assessment (EIA) roots. Scholars have argued the need to conceptualize SEA as a process designed to facilitate strategic thinking, thus enabling transitions toward sustainability. The practice of SEA, however, remains deeply rooted in the EIA tradition and scholars and practitioners often appear divided on the nature and purpose of SEA. This paper revisits the strategic principles of SEA and conceptualizes SEA as a multi-faceted and multi-dimensional assessment process. It is suggested that SEA can be conceptualized as series of approaches operating along a spectrum from less to more strategic – from impact assessment-based to strategy-based – with each approach to SEA differentiated by the specific objectives of SEA application and the extent to which strategic principles are reflected in its design and implementation. Advancing the effectiveness of SEA requires a continued research agenda focused on improving the traditional SEA approach, as a tool to assess the impacts of policies, plans and programs (PPPs). Realizing the full potential of SEA, however, requires a new research agenda — one focused on the development and testing of a deliberative governance approach to SEA that can facilitate strategic innovations in PPP formulation and drive transitions in short-term policy and initiatives based on longer-term thinking. •SEA facilitates strategic thinking, enabling transitions toward sustainability.•SEA is conceptualized as a spectrum of approaches, from IA-based to strategy-based.•Each approach variably emphasizes strategic principles in its design and practice.•There is no one conceptualization of SEA that is best, SEA is fit for PPP purpose.•Research is needed to advance SEA to facilitate strategic PPP transformations.